THE LITERARY PRODUCTION IN THE CUBAN RELIGIOUS IMAGINARY - Saldívar Arellano, Juan Manuel (2016)
The cuban literary production (antillana o afronegrista), it was land mark, beside a realwonderfull time in live also a relevant analysis that helped to understood the singularityof the cuban religious manifestation. How that is the African ancestors have developedmultiple cultural identities from the mystical Gran Caribe and the Antillas. In regards tothe Cuban case, we can confirm the identification of a black person a part of an extensivediscussion that leads to understand the cultural situation in a vast sense of the meaning.Finally, the horizontal symbolic mixed; of the point view of literature it´s relevant in thesense to extended, not only the theme of the discussion, even though future statementbetween the imaginative, the representative and the real existent.